Master Mould an Copy Room - De Wolf, Hans M; CAFA Art Museum, Beijing; D'hooghe, Joris; Chaffee, Cathleen; Tuymans, Luc; Chiacchio, Francesca; Vanschoonbeek, Francesca; Gerits, Loes ([S.l.] : [s.n.], 2014)
Alÿs, Francis ; Becher, Bernd ; Becher, Hilla ; Bijl, Guillaume ; Broodthaers, Marcel ; Duchamp, Marcel ; Höfer, Candida ; Gongkai, Pan ; Rombouts, Guy ; Dong, Song ; Schwind, Jean ; Sturtevant, Elaine ; Yuan, Sun ; Yu, Peng ; Xinpeng, Su ; Theys, Frank ; Tuerlinckx, Joëlle ; Van de Velde, Rinus ; Vermeiren, Didier ; Bing, Xu
Vrije Universiteit Brussel, Wintergarten Research Group en CAFA Art Museum Beijing, 2014.10.21 - 11.23
kunstcatalogus